119k views
0 votes
What is 5/8p = 9/4 - 3/8​

User Raf
by
5.3k points

2 Answers

2 votes

p in (-oo:+oo)

(5/8)*p = 9/4-(3/8) // - 9/4-(3/8)

(5/8)*p-(9/4)+3/8 = 0

(5/8)*p-9/4+3/8 = 0

5/8*p-15/8 = 0 // + 15/8

5/8*p = 15/8 // : 5/8

p = 15/8/5/8

p = 3

p = 3

User Phat Huynh
by
5.6k points
4 votes

Answer:

p in (-oo:+oo)

(5/8)*p = 9/4-(3/8) // - 9/4-(3/8)

(5/8)*p-(9/4)+3/8 = 0

(5/8)*p-9/4+3/8 = 0

5/8*p-15/8 = 0 // + 15/8

5/8*p = 15/8 // : 5/8

p = 15/8/5/8

p = 3

p = 3

Explanation:

User Khabir
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.